Estimating the neutron component of radiation properties of the IVG.1M research reactor irradiated low-enriched fuel; Applied Radiation and Isotopes; Vol. 181 - Irkimbekov R. A. Ruslan Aleksandrovich; Vurim A. D. Aleksandr Davidovich; Bedenko S. V. Sergey Vladimirovich; Vlaskin G. N. Gennadiy Nikolaevich; Suraev A. S. Artur Sergeevich; Vityuk G. A. Galina Anatoljevna; Vega-Carrillo H. R. Hector Rene (2022, 2022)
Title screen